Focal spot imaging based on zero lag cross‐correlation amplitude fields: Application to dense array data at the San Jacinto fault zone. Issue 11 (10th November 2016) - Hillers, G.; Roux, P.; Campillo, M.; Ben‐Zion, Y.
Abstract: We image the subsurface below a dense seismic array straddling the Clark branch of the San Jacinto fault zone in Southern California. The analysis is based on focal spots of surface waves associated with the zero lag amplitudes of noise cross‐correlations computed between all stations of the dense array. Local medium properties are inferred from the spatially variable focal spot size and shape based on the first zero crossing of amplitude versus distance distributions. The method provides simultaneous estimates of wave speed, apparent attenuation, and anisotropy without solving a tomographic inverse problem. The obtained images of the frequency dependent seismic velocity distributions are consistent with independent estimates from a far‐field Rayleigh wave tomography. We observe an anticorrelation between our apparent attenuation coefficient and seismic velocity, and a fault‐parallel alignment of fast propagation directions with greater structural complexity to the southwest of the fault. The results imply a complex fault zone structure including a waveguide to the northeast of the fault that is continuous across the observed depth range and a low‐velocity structure to the southwest associated with a shallow sedimentary basin. Key Points: Two‐dimensional surface wave focal spots are reconstructed from noise correlation functions Properties of the focal spot are controlled by local medium properties Wave speed, anisotropy, and apparent attenuation are estimated simultaneously